Comparative Efficiency Analysis of Referral Costs in - Portela, Maria (2010)
The aim of this paper is to compare English General Practitioner (GP) units in terms of their overall referral costs through Data Envelopment Analysis (DEA). Results revealed potential cost savings and benchmark practices under 4 perspectives: ‘overall cost efficiency’, ‘technical efficiency’, ‘allocative efficiency’, and ‘price efficiency’.